An evaluation of mat hybrid turfgrass systems under simulated traffic. Issue 1 (29th April 2021) - Thoms, Adam W.; Bearss, Ryan; Rogers, John N.; Sorochan, John C.
Abstract: The addition of synthetic fibers to natural grass athletic fields forms a hybrid turf system, and this system claims to increase traffic tolerance and playability. The objectives of this research were to evaluate the physical effects of simulated traffic on two hybrid, carpet‐based mat systems (Eclipse and Hero) with Kentucky bluegrass ( Poa pratensis L.), compared to a non‐hybrid control (100% Kentucky bluegrass). Field research was conducted in 2018 at Michigan State University (MSU), Iowa State University (ISU) and the University of Tennessee (UT) to evaluate the percent green cover, surface hardness, and shear resistance under 25 simulated traffic events (STE). Percent green cover across all treatments was reduced after 25 STE. After 25 STE the hybrid systems had greater percent green cover (Eclipse 49% and Hero 48%) than the non‐hybrid control (33%) at the ISU location. Surface hardness values differed between treatments on many rating dates. The hybrid systems reported higher surface hardness values, but these values were never above 100 Gmax. These results indicate that the Eclipse and Hero systems can offer a safe and stable surface even if turfgrass cover is reduced. Core Ideas: New hybrid mat systems need research Surface hardness values were never above 100 GMAX for any treatment Hero and Eclipse mat systems perform similar to natural grass